Association between dyslipidemia and vitamin D deficiency: a cross-sectional study in Chinese healthy population - Li, Bin; Wang, Jianhong; Xu, Jialie; Xie, Jianying; Liu, Quanyong; Yang, Chenxi; Zhang, Zhengmao (Frontiers in Endocrinology, 2025)
BackgroundGiven the global prevalence of vitamin D deficiency, this study examines the association between serum 25-hydroxyvitamin D (25(OH)D) levels and lipid profiles, including total cholesterol, low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and triglycerides (TG).MethodsIn a cross-sectional analysis at the Yuhuan People’s Hospital Physical Examination Center, 1535 asymptomatic individuals underwent anthropometric assessment and blood sampling. Serum 25(OH)D levels were quantified by a chemiluminescent immunoassay, while lipid parameters were evaluated by an enzymatic method on a fully automated analyzer.ResultsThe mean serum 25(OH)D level of the participants was 49.6 ± 15.3 nmol/L, with 54.7% demonstrating vitamin D deficiency. Female participants had significantly lower mean 25(OH)D levels (46.2 ± 13.7 nmol/L) than males (54.1 ± 16.0 nmol/L, P < 0.001). After adjustment for age and BMI, multivariate ordinal logistic analysis revealed a 1.71-fold higher dyslipidemia-associated risk of vitamin D deficiency in the population (OR=1.71, 95% CI=1.07-2.79), more pronounced in females(OR=2.84, 95% CI=1.17-8.09) compared to males (OR=1.44, 95% CI=0.82-2.58). Notably, vitamin D deficiency was significantly associated with elevated LDL-C levels in females (OR=5.17, 95% CI=1.47-32.96), in contrast to males.ConclusionThis study highlights a significant association between 25(OH)D deficiency and an increased risk of dyslipidemia, especially in females, highlighting the importance of considering gender-specific risk factors in the management of 25(OH)D deficiency.